Presentation of Childhood Systemic Lupus Erythematosus in a Tertiary Care Hospital (Bangladesh Journal of Child Health, 2015)
Background: Systemic lupus erythematosus in children (Paediatric SLE / pSLE) may have a great variability in disease presentation. Any organ system can be involved in pSLE leading to protean clinical manifestations.To evaluate the clinical and serological presentation of pSLE in tertiary renter Bangladesh and to compare it with other populations. Methodology: It was a retrospective cohort study carried out in the department of Paediatrics, Bangabandhu Sheikh Mujib Medical University, Dhaka during the period of January 2005 to December 2013. A total of 70 patients fulfilling the 1997 revised ACR classification criteria for SLE were enrolled in the study. Data was collected in a pre-designed questionnaire. Results: Age range was 2.5 years to 16 years, female: male ratio was 7:1. Duration of disease was 1 month to 18 months. Common clinical presentation included general weakness/fatigue (91%), fever (83%), arthralgia/arthritis (74%), oral ulcer (73%) and skin rash (71%). All the patients were anemic. ANA was positive in 97% cases and anti-ds DNA in 91% cases. More than 65% cases had evidences of renal involvement at the presentation. Among the patients who underwent kidney biopsy, 40% had diffuse proliferative lupus nephritis (WHO class IV) followed by class III in 26% cases. Conclusion: Pediatric SLE patients in our country, compared to other countries had much higher incidence of fever and non-specific complaints such as, general weakness and malaise as presenting symptoms. Thus, a strong index of suspicion should be maintained for early diagnosis of pSLE especially among adolescent girls. DOI: http://dx.doi.org/10.3329/bjch.v38i3.22819 Bangladesh J Child Health 2014; VOL 38 (3) :124-129